Demographics of Rhesus Phenotype of Blood Donors in Calabar: A Case Study of University of Calabar Teaching Hospital, Calabar, Cross River State, Nigeria - Joyce Ezekiel Etura; Rose A. Amaechi; Josephine O. Akpotuzor; Henshaw Uchechi Okoroiwu (Advances in Hematology, 2020)
Background. Rhesus antigens have been documented to cause haemolytic disease of the newborn as well as acute and delayed transfusion reactions. This study was performed to evaluate the frequency of rhesus antigens (C, c, D, E, and e) in the studied population. Method. This study was a cross-sectional study involving 130 prospective blood donors attending University of Calabar Teaching Hospital (UCTH) donor clinic. Donors were grouped for Rh antisera (anti-E, anti-e, anti-C, anti-c, and anti-D) using the standard serologic technique. Result. The most prevalent Rh antigen was “c” (98.5%), followed by “D” (97.7%), while the least was “C” (30.7%). The most prevalent phenotype was cDe/cDe (R0R0). Conclusion. This work therefore concludes that the most prevalent rhesus antigen and rhesus phenotype was c and cDe/cDe among blood donors in University of Calabar Teaching Hospital.